Ammonothermal Synthesis of Crystalline Oxonitride Perovskites LnTaON2 (Ln=La, Ce, Pr, Nd, Sm, Gd). Issue 47 (1st August 2017) - Cordes, Niklas; Schnick, Wolfgang
Abstract: The perovskite type oxonitridotantalates LnTaON2 with Ln=La, Ce, Pr, Nd, Sm, and Gd were synthesized by the ammonothermal method employing custom‐built autoclaves made of nickel‐based superalloy. Metal powders were reacted with NaOH and NaN3 as mineralizers under supercritical conditions with purified ammonia at temperature range of 870–1070 K and pressure values of 150–300 MPa. Crystal structures and the space groups were determined by using powder X‐ray diffraction and refined by the Rietveld method. The refined lattice parameters are for LaTaON2 ( a= 5.7156(1), b= 8.0675(1), c= 5.7465(1) Å, R wp =0.0471), CeTaON2 ( a= 5.6761(11), b= 8.0386(16), c= 5.7891(12) Å, R wp =0.183), PrTaON2 ( a= 5.6920(1), b= 8.0197(1), c= 5.6804(1) Å, R wp =0.0349), NdTaON2 ( a= 5.6884(1), b= 8.0037(2), c= 5.6554(1) Å, R wp =0.026), SmTaON2 ( a= 5.6827(1), b= 7.9656(2), c= 5.6103(1) Å, R wp =0.042), GdTaON2 ( a= 5.6160(10), b= 7.9359(12), c= 5.5962(10) Å, R wp =0.118). LaTaON2 crystallizes in space group Imma (no. 74) and the other compounds LnTaON2 with Ln=Pr, Nd, Sm, Gd in Pnma (no. 62). SEM measurements were performed to investigate the elemental composition and morphology of the oxonitride perovskites. The bandgap values of the oxonitrides (LaTaON2 1.8 eV, CeTaON2 1.7 eV; PrTaON2 1.9 eV, NdTaON2 2.0 eV, SmTaON2 2.0 eV, GdTaON2 1.8 eV) were estimated by using UV/Vis measurements and the Kubelka–Munk function. Abstract : Perovskite phases : Highly crystalline oxonitride perovskites (LnTaON2 Ln=La, Ce, Pr, Nd, Sm, Gd) were synthesized by the ammonothermal approach in custom‐built high‐pressure autoclaves at relatively low temperatures between 870–1070 K and pressures of up to 300 MPa. This more sophisticated route requires no precursor and gave cube‐like crystals up to 15 μm (see scheme).